Poly (ADP-ribose) polymerase 1 (PARP1) and its DNA-binding characteristics - Kramer, Michael A., author; Luger, Karolin, advisor; Woody, Robert, committee member; Bailey, Susan M., committee member (Colorado State University. Libraries, 2011)
The poly(ADP-ribose) polymerase (PARP) family is evolutionarily diverse, containing 18 different protein members. Roles played by PARP1 in the cell appear to be significant in establishing cellular complexity, as a correlation exists between higher eukaryotes and prevalence of PARP family members. Each member of the PARP family contains a conserved catalytic domain, which upon activation cleaves molecules of NAD+ to form polymers of ADP-ribose, with the release of nicotinamide. Poly(ADP-ribosyl)ation reactions carried out by PARP family members have been found to function in regulation of cellular systems including DNA-damage repair, transcription, mitotic spindle formation, telomere maintenance and cell-death signaling. The most well established member of the PARP family is poly(ADP-ribose) polymerase 1 or PARP1. PARP1 has been found to associate with an assortment of DNA structures within the cell. Despite being able to complex with any DNA present in the cell, PARP1 displays a propensity to interact with sites of DNA-damage. As such, PARP1 has been found to play a major role in initiation of DNA-damage repair. Through its catalytic activity PARP1 recruits additional DNA-damage repair machinery and promotes exposure of the site of damage through chromatin relaxation. Due to its ability to regulate chromatin structure, PARP1 has also been frequently connected with transcription regulation. Variable regulation of transcription by PARP1 has been observed. Catalytically inactive PARP1 can function in a similar fashion as the protein H1 to condense chromatin. Alternatively, active PARP1 functions to relax chromatin surrounding promoter regions and recruit transcription machinery. PARP1 activity appears to be primarily regulated through its association with DNA. Little is known regarding PARP1-DNA-binding affinity. Here I present a high-throughput in-solution FRET-based assay that I utilize to better characterize PARP1's interaction with sites of DNA-damage. In addition, the PARP1-nucleosome complex was analyzed utilizing the same FRET-based assay. Discrepancies found between PARP1 binding affinities to various DNA-damage and mononucleosome constructs provide insight into a potential variable mode of interaction exhibited by PARP1.
Keywords: DNA-binding; PARP1; PARP